Wood-Destroying Insects - P.G. Koehler; J.L. Castner (EDIS)
This document provides an overview of various wood-destroying insects, including Lyctid, Bostrichid, and Anobiid powderpost beetles, old house borers, Formosan termites, drywood termites, Eastern subterranean termites, carpenter ants, and carpenter bees. It describes their physical characteristics, life cycles, and the types of wood they infest. The publication emphasizes the importance of identifying these pests for effective management and control. Date first printed January 1996.